On a five-dimensional scenario of massive gravity - Tuan, Do Quoc (VNU Journal of Science: Mathematics - Physics, 2017)
Abstract. A study on a five-dimensional scenario of a ghost-free nonlinear massive gravity proposed by de Rham, Gabadadze, and Tolley (dRGT) will be presented in this article. In particular, we will show how to construct a five-dimensional massive graviton term using the Cayley-Hamilton theorem. Then some cosmological solutions such as the Friedmann-Lemaitre-Robertson-Walker, Bianchi type I, and Schwarzschild-Tangherlini-(A)dS spacetimes will be solved for the five-dimensional dRGT theory thanks to the constant-like behavior of massive graviton terms under an assumption that the reference metric is compatible with the physical one. Keywords: Massive gravity, higher dimensions, Friedmann-Lemaitre-Robertson-Walker, Bianchi type I, and Schwarzschild-Tangherlini-(A)dS spacetimes